Proactive interference of open field on consummatory successive negative contrast - Justel, Nadia (2014)
Reactivity to a reward is affected by prior experience with the different reinforcer values of that reward, a phenomenon known as incentive relativity, which can be studied using the consummatory succesive negative contrast (cSNC) paradigm, in which the performance of animals that receive a 4 % sucrose solution after trials on which they were exposed to 32 % sucrose is compared with that of subjects that always receive the 4 % sucrose solution. The exploration of a novel open field can enhance or block the acquisition of associative and nonassociative memories. The effect of open field on cSNC has not yet been explored. The main result of the present study was that open-field exposure significantly modified the expression of cSNC. Exposure to an open field 1 h but not immediately before the downshift interfered with the expression of cSNC. These animals drank more of the downshifted reward than did controls that were not exposed to the apparatus, and this behavior persisted for up to three recovery trials. This phenomenon was observed even when the animals were given a more protracted preshift phase and when the discrepancy between the preshift and shift incentive values of sucrose were increased. An open field also interfered with incentive downshift when open-field exposure occurred 6 h before the downshift, and repeated exposure to the apparatus did not deteriorate this effect. The present study adds to a growing body of literature that indicates that open-field exploration can interfere with memory formation.